Lectures problems and solutions for ordinary differential equations - Deng, Yuefan (Singapore World Scientific, 2015)
This unique book on ordinary differential equations addresses practical issues of composing and solving such equations by large number of examples and homework problems with solutions. These problems originate in engineering, finance, as well as science at appropriate levels that readers with the basic knowledge of calculus, physics or economics are assumed able to follow.
Keywords: Differential equations